I Am Somebody. Paul's Roman Rhetoric - Chapman, Dean W. (Protokolle zur Bibel, 2000)
The paper argues from social science, orality and rhetorical perspectives that Paul, as a first-century Mediterranean orator, is trying to embed himself as an authority in the Roman Christian community, using writing - almost against his will - in place of a personal visit. A logical reason why he should do so emerges from his own particular situation as he prepares to leave Corinth for Jerusalem with the "collection." Paul anticipates a transfer to Rome if he is arrested in Jerusalem, and desires that at least one "group" in Rome know Paul as God's ambassador before he is introduced to them as a prisoner of the State, and a pariah of his own kin.